Synthesis, characterization and pharmacological evaluation of different 1,3,4-oxadiazole and acetamide derivatives of ethyl nipecotate - Khadija Nafeesa; Aziz-; Muhammad A. Abbasi; Sabahat Z. Siddiqui; Shahid Rasool; Syed A.A. Shah (Faculty of Pharmacy, Cairo University, 2017)
A new series of N-substituted derivatives of 2-[(5-{1-[(4-chlorophenyl)sulfonyl]-3-piperidinyl}-1,3,4-oxadiazol-2-yl)sulfanyl]acetamide (6a-w) has been designed and synthesized with multifunctional moieties. The synthesized compounds were evaluated for their antibacterial and anti-enzymatic potential supported by % hemolytic activity. The synthesized compound 5-(1-(4-chlorophenylsulfonyl)-3-piperidinyl)-1,3,4-oxadiazole-2-thiol (3) was stirred with synthesized electrophiles as N-aryl/alkyl/aralkyl-2-bromoacetamide (5a-w) in an aprotic solvent under basic conditions to acquire the target molecules, 6a-w. The spectral analytical techniques of IR, EI-MS, 1H NMR and 13C-NMR were utilized for structural elucidation of synthesized molecules. The antibacterial screening against certain bacterial strains of gram-negative and gram-positive bacteria rendered compound 6i as good inhibitor of gram-negative bacterial strains. The enzyme inhibition revealed low potential against lipoxygenase (LOX) enzyme. The hemolytic study provided valuable information about cytotoxic behavior of synthesized molecules. Keywords: 1,3,4-Oxadiazole, Acetamide, Antibacterial activity, Hemolytic activity, Lipoxygenase inhibition